#### Answer

$(7x-2)(3x-1)$

#### Work Step by Step

$21x^{2}−13x+2$
First, identify two numbers that multiply with each other to become 42, the product of the constant and coefficient of x2 (21 × 2) and add together to become -13, the coefficient of x.
From inspection, we identify these numbers as -6 and -7.
Secondly split the coefficient of x into the sum of the two above numbers.
$21x^{2}−13x+2$
$=21x^{2}+(-6-7)x+2$
$=21x^{2}-6x-7x+2$
Factorize by grouping to find the answer.
$21x^{2}-6x-7x+2$
$=3x(7x-2)-(7x-2)$
$=(7x-2)(3x-1)$